Robust dynamic ID–based remote user authentication scheme using smart cards. (22nd December 2014) - Li, Xiong; Niu, Jianwei; Liu, Yazhi; Liao, Junguo; Liang, Wei
Smart card–based password authentication scheme is one of the most simple and efficient method to identify the legitimacy of a user via an insecure channel. To protect the user from tracking by the attacker, many dynamic ID–based user authentication schemes have been proposed. Recently, Chen et al. proposed an efficient and secure dynamic ID–based authentication scheme using smart cards. However, we find that Chen et al.'s scheme cannot really protect user's anonymity and forward secrecy. Besides, their scheme is inefficient in the authentication phase and cannot resist stolen smart card attack. In this paper, we propose a robust dynamic ID–based user authentication scheme using smart cards to cover the above weaknesses, the proposed scheme can really protect the user's anonymity and is more secure comparing with other related schemes.